2001
DOI: 10.1096/fj.00-0619fje
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to HIV‐1 infection among African sex workers is associated with global hyporesponsiveness in interleukin4 production

Abstract: We previously identified HIV‐1 resistant prostitutes who remain persistently HIV‐1 PCR‐ and antibody‐negative despite continued heavy exposure to HIV‐1 through sex work. We hypothesized that differences in virus‐specific cytokine responses are associated with resistance vs. susceptibility to infection. Although polyclonal activation failed to reveal such differences, antigen‐mediated activation of peripheral blood mononuclear cells (PBMC) in primary culture by using intact HIVIIIB demonstrates that resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
8
1
Order By: Relevance
“…Instead, the protective phenotype is associated with adaptive cellular and mucosal responses to HIV, reduced systemic immune activation, and an elevated frequency of regulatory T cells compared to HIV-uninfected controls (1,2,12,(23)(24)(25)50). These HESN women have elevated expression of HIV inhibitory factors at the genital tract, including serpins, other antiproteases, SLPI, and RANTES, as well as several undefined factors (11,21,22,50). In addition, endogenous antiretroviral elements, such as APOBECs and TRIM-5␣, may also be important in resistance to HIV infection.…”
mentioning
confidence: 99%
“…Instead, the protective phenotype is associated with adaptive cellular and mucosal responses to HIV, reduced systemic immune activation, and an elevated frequency of regulatory T cells compared to HIV-uninfected controls (1,2,12,(23)(24)(25)50). These HESN women have elevated expression of HIV inhibitory factors at the genital tract, including serpins, other antiproteases, SLPI, and RANTES, as well as several undefined factors (11,21,22,50). In addition, endogenous antiretroviral elements, such as APOBECs and TRIM-5␣, may also be important in resistance to HIV infection.…”
mentioning
confidence: 99%
“…The findings by Trivedi et al [8] that a subgroup of the Kenyan APSWs that are resistant to HIV-1 infection are hypo-producers of IL-4 provided the reason for their resistance to HIV-1 infection. The low level of IL-4 production may suggest that these women may have an early stop codon mutation in the gene that inhibits the synthesis of both IL-4 and IL-4 delta 2 splice variant.…”
Section: Hypothesis: Over-production Of Il-4 Delta 2 May Cause Hiv-1 mentioning
confidence: 98%
“…Trivedi et al [8] studied the levels of Thl and Th2 cytokines in the serum of the HIV-1 resistant APSWs in Kenya. It was reported that they exhibited enhanced level of Interferon gamma but a very low level of the Th2 cytokine IL-4.…”
Section: Studies On Hiv-1 Resistant Apsws In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Interferon regulatory factor 1 (IRF-1), the first-identified member of the IRF family, was originally defined as a transcription regulator of IFN-b (Fujita et al 1989(Fujita et al , 1988. Later studies showed that IRF-1 function was not restricted to the IFN pathway but, rather, by binding an interferonstimulated response element (ISRE) present in the promoters of IFN-stimulated genes (ISG), IRF-1 could regulate multiple immune genes' expression and is broadly involved in both innate and adaptive immunity, especially in the regulation of Th1/Th2 differentiation, which may affect resistance to HIV-1 infection (Kroger et al 2002;Lohoff et al 1997;Mamane et al 1999;Taki et al 1997;Taniguchi et al 2001;Trivedi et al 2001). The human IRF-1 gene, spanning 7.72 Kb with its 495 bp immediate upstream promoter sequence, has been assigned to 5q31.1 (Harada et al 1994;Itoh et al 1991).…”
Section: Introductionmentioning
confidence: 99%